A Review of Nanostructured Ion‐Exchange Membranes. Issue 10 (22nd April 2021) - Shehzad, Muhammad A.; Yasmin, Aqsa; Ge, Xiaolin; Wu, Liang; Xu, Tongwen
Abstract: Ion‐exchange membranes (IEMs) with tunable nanostructures possess great potential for energy‐efficient use in various applications such as electrodialysis, fuel cells, secondary batteries, and so on. Insight into the relationship between the morphology of the membrane nanostructures and the ions permeation is key to the realistic design and advancement of nanostructured IEMs. Here, recent progress on broadly divided four types of IEMs, based on solid‐state nanostructures, self‐assembled nanochannels, fillers‐integrated nanostructures, and artificial surface structures, are highlighted. For each type, fabrication of the nanostructured membranes and their influence on physical and ion transport properties are summarized. Additionally, the potential perspective of the nanostructured IEMs′ engineering and application are discussed in this review. Abstract : Ion‐exchange membranes (IEMs) with tunable nanostructures possess great potential for energy‐efficient use in various ions separation, energy generation, and energy storage applications. This review summarizes recent progress on the fabrication and ion‐exchange properties of broadly divided four types of IEMs, based on solid‐state nanostructures, self‐assembled nanochannels, fillers‐integrated nanostructures, and artificial surface structures.